2016
DOI: 10.6118/jmm.2016.22.2.76
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal Osteoporosis Is Associated with Serum Chemerin and Irisin but Not with Apolipoprotein M Levels

Abstract: ObjectivesThe objective of this study was to describe the levels of chemerin, irisin and apolipoprotein M (apoM) in women with postmenopausal osteoporosis.MethodsThe study included 88 women with postmenopausal osteoporosis. Based on World Health Organization criteria, women with a T-score of ≤ –2.5 were defined as osteoporotic. In this case-control study, postmenopausal women with T-score > –1 were selected as controls (n = 88) and case-matched in a 1:1 ratio based on age (within 2 years) and body mass index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 12 publications
0
23
1
Order By: Relevance
“…Engin-Üstün et al (28) reported that serum irisin levels were significantly lower in women with postmenopausal osteoporosis than in postmenopausal controls. Anastasilakis et al (29) and Palermo et al (30) found that a lower level of serum irisin was associated with osteoporotic fractures in postmenopausal women, implying that irisin may suppress osteoclastogenesis because the remarkable pathologic change in postmenopausal osteoporosis is increased osteoclastogenic activity.…”
Section: Discussionmentioning
confidence: 98%
“…Engin-Üstün et al (28) reported that serum irisin levels were significantly lower in women with postmenopausal osteoporosis than in postmenopausal controls. Anastasilakis et al (29) and Palermo et al (30) found that a lower level of serum irisin was associated with osteoporotic fractures in postmenopausal women, implying that irisin may suppress osteoclastogenesis because the remarkable pathologic change in postmenopausal osteoporosis is increased osteoclastogenic activity.…”
Section: Discussionmentioning
confidence: 98%
“…Osteoporosis is known to be affected by numerous factors, including ethnic origin, socioeconomic status, diet, physical activity, lifestyle, alcohol and drug abuse, and insufficient exposure to sunlight. 1 , 2 Moreover, postmenopausal osteoporosis is associated with adolescent pregnancy, number and frequency of parity, and duration and frequency of lactation. 2 The mainstay diagnosis of osteoporosis is based on the assessment of BMD at the femoral neck and the anterior–posterior lumbar spine using dual-energy X-ray absorptiometry (DXA).…”
Section: Introductionmentioning
confidence: 99%
“…1 , 2 Moreover, postmenopausal osteoporosis is associated with adolescent pregnancy, number and frequency of parity, and duration and frequency of lactation. 2 The mainstay diagnosis of osteoporosis is based on the assessment of BMD at the femoral neck and the anterior–posterior lumbar spine using dual-energy X-ray absorptiometry (DXA). 1 , 2 A T-score ≤−2.5 standard deviation (SD) is considered osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, evidence suggests that irisin also contributes to bone metabolism (4)(5)(6). Both bone mass and bone quality of mice, with or without osteoporosis, were improved after irisin treatment (7).…”
Section: Introductionmentioning
confidence: 99%